'Manufacturing or Services - That is (not) the Question' The Role of Manufacturing and Services in OECD Economies - De Backer, Koen (OECD Science, Technology and Industry Policy Papers, 2015)
Manufacturing features again high on the policy agenda in a lot of OECD countries. While deindustrialisation and offshoring have dominated the news about manufacturing during the past decades, recent years have witnessed a number of examples of companies re-shoring activities back to OECD economies. It is then not surprising that the discussion about the need for industrial policies in favour of manufacturing has gained importance in recent years. Policy discussions however often ignore the profound changes manufacturing has undergone in recent years, for example manufacturing today is much more than the pure production of tangible things and includes a growing services content. This paper addresses this issue against the background of long-term structural change of OECD economies and discusses the changing role of manufacturing and services in OECD economies